Amphiphilic functional block copolymers bearing a reactive furfuryl group via RAFT polymerization; reversible core cross-linked micelles via a Diels–Alder "click reaction". Issue 3 (4th January 2016) - Pramanik, Nabendu B.; Singha, Nikhil K.
Abstract : Amphiphilic BCPs, PFMA- b -PPEGMA were prepared via RAFT polymerization. They were self-assembled into micelles in aqueous medium with a hydrophobic PFMA core and hydrophilic PPEGMA corona. Core cross-linked micelles were prepared via the DA reaction. Abstract : Amphiphilic diblock copolymers of poly(furfuryl methacrylate) (PFMA) and poly(polyethylene glycol methyl ether methacrylate) (PPEGMA) (PFMA- b -PPEGMA) were prepared via reversible addition fragmentation chain-transfer (RAFT) polymerization by using PFMA as a macro-RAFT agent. In water, the amphiphilic diblock copolymer, poly(FMA- b -PEGMA) (PFP ) formed micelles with PFMA in the core and PPEGMA in the corona. Diels–Alder chemistry was carried out to crosslink the hydrophobic PFMA core by using bismaleimide in water at 60 °C. The de-crosslinking of hydrophobic PFMA core was carried out upon heating the samples at 150 °C for 30 min via retro-DA reaction which was confirmed by 1 H-NMR analysis.